2022
DOI: 10.1021/acsami.2c14815
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Liquid Metal Embedded Elastomers for Soft Thermal and Electrical Materials

Abstract: Liquid metal embedded elastomers (LMEEs) are composed of a soft polymer matrix embedded with droplets of metal alloys that are liquid at room temperature. These soft matter composites exhibit exceptional combinations of elastic, electrical, and thermal properties that make them uniquely suited for applications in flexible electronics, soft robotics, and thermal management. However, the fabrication of LMEE structures has primarily relied on rudimentary techniques that limit patterning to simple planar geometrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Recently, liquid metal-based composites are developed to resolve these limitations. To fabricate soft composite, liquid metals are normally smashed into small particles through ultrasonication and blended with mechanical backbones such as polymer matrices ,, or metal nanowires. , For example, the surface of liquid metal nanoparticles was functionalized for uniform blending with polymer matrix and surface-initiated atom transfer radical polymerization (Figure A) . Through surface modification, a uniform blending of nanoparticles was possible for various polymer matrices.…”
Section: Bridging Interface With the Human Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, liquid metal-based composites are developed to resolve these limitations. To fabricate soft composite, liquid metals are normally smashed into small particles through ultrasonication and blended with mechanical backbones such as polymer matrices ,, or metal nanowires. , For example, the surface of liquid metal nanoparticles was functionalized for uniform blending with polymer matrix and surface-initiated atom transfer radical polymerization (Figure A) . Through surface modification, a uniform blending of nanoparticles was possible for various polymer matrices.…”
Section: Bridging Interface With the Human Bodymentioning
confidence: 99%
“…Together with composite techniques, high-resolution grid patterning is an alternative approach to utilizing liquid metal as transparent conductors. Photolithography, laser sintering, , and 3D printing are recently reported to fabricate micropatterned liquid metal composites. Liquid metal composite fabricated by lithography showed over 500% of strain without loss of its electrical conductivity.…”
Section: Bridging Interface With the Human Bodymentioning
confidence: 99%
“…Recently, liquid metals have received widespread attention in the sensing field due to their unique mechanical, electrical, thermal and optical properties. [118][119][120][121][122] Compared to other soft or conductive materials, liquid metals can make electronics more accessible to the tissues, human body and clothing while maintaining mechanical flexibility. Kim et al reported a freestanding patterned liquid metal thin-film conductor (FS-GaIn).…”
Section: Electrode Materials Compositionmentioning
confidence: 99%
“…45 Yet, all the prepared microchannels are quadrilateral cross-sections, whose deformation rate is also restrained. Moreover, the depth-width ratio of microchannels prepared by photolithography is limited by the thickness of cured photoresist, 46 whereas the microchannels by laser engraving are unsmooth and irregular because of the uneven laser focusing. 33 Also, when casting microchannels with large depth-width ratios by using the molding method, the demolding process often results in the tearing of materials.…”
Section: Introductionmentioning
confidence: 99%